Molecular weight effects of PEG on the crystal structure and photocatalytic activities of PEG-capped TiO2 nanoparticles. Issue 86 (2nd September 2016) - Zhang, Meizhou; Lei, Jinfeng; Shi, Yifeng; Zhang, Lina; Ye, Youxin; Li, Defu; Mu, Changdao
Abstract : The increasing molecular weight of PEG can increase the water dispersion but decrease the photocatalytic activity of PEG-capped TiO2 . Abstract : Polyethylene glycol (PEG) was used as stabilizer to prepare water-soluble anatase titanium dioxide (TiO2 ). The molecular weight effects of PEG on the crystal structure and photocatalytic activities of PEG-capped TiO2 nanoparticles were systematically studied. The results show that the steric hindrance effect of PEG molecular chains will hinder the PEG molecules from being tied to the surface of TiO2, resulting in the decrease of PEG molecules capped on the surface of TiO2 with the growth of PEG molecular chains. It is significant that PEG can effectively promote the dispersion of TiO2 nanoparticles in water, which becomes better and better with the increase of molecular weight of PEG. Moreover, the PEG-capped TiO2 aqueous solutions can keep stable for more than two months. PEG cannot influence the crystal type and size of TiO2, which can be well controlled by the introduction of HCl in the reaction system. The photocatalytic activity of PEG-capped TiO2 was evaluated by monitoring the degradation of methyl orange, which is better than that of commercial P25 TiO2 mainly due to the good dispersion in water. However, PEG molecular chains are detrimental to the transfer of photogenerated electrons and reactive oxygen species while the increasing dispersion in water with the increase of PEG molecular weight can increase the photocatalytic activity of TiO2 . As a result, PEG400 capped TiO2 presents the best photocatalytic activity while PEG2000 capped TiO2 exhibits the worst photocatalytic activity. The photocatalytic activity begins to increase when the molecular weight of PEG is larger than 2000.